REDEFINING BEAUTY STANDARD IN LAKSMI PAMUNTJAK’S THE QUESTION OF RED - Yulia Eka Pristiana; Much Koiri (English Letter Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The word